[Arbaʻīn-i Jāmī , 1256, i.e. 1840 or 1841]. - Jāmī; Muḥammad Zakarīyā Samarqandī (Title from colophon:اربعین حدیث مع ترجمه, 1840)
Elegant copy of Jāmī's verse paraphrase of forty ḥadīth.
Shelfmark: Ann Arbor, University of Michigan, Special Collections Research Center, Isl. Ms. 432
Origin: As appears in colophon, copied by Muḥammad Zakarīyā Samarqandī with transcription completed in the year 1256 [1840 or 41].
Former shelfmark: "548 T. De M. [i.e. Tammaro De Marinis]" inscribed in pencil on recto of front flyleaf ; "233" inscribed in pencil on 'title page'.
Binding: Heavy pasteboards covered in painted lacquerwork, spine in black leather ; Type III binding (without flap) ; doublures in fine painted lacquerwork of composition evoking book cover design with central mandorla and pendants (filled with flowers and leaves in shades of pink and green on a black ground) set in a red ground with swirling floral vegetal pattern in gold and surrounded by border in black with white dots and flanking gold fillets (composition of upper doublure mirrors that of lower doublure) ; upper and lower covers bear paintings of nearly identical floral composition in mirror image to one another on an orange or bronze background, namely a central cluster of peonies, poppies, etc. with roses, poppies, buds, and other floral forms all in shades of pink and white with leaves in various shades of green, and surrounded by decorative bands with floral motifs in various sizes on bands of red and black ; sewn in pink thread, four stations ; overall in fair condition with some abrasion and losses to lacquerwork and pasteboard, text block almost fully detached from cover, etc. ; cover large for textblock and perhaps not original.
Support: Quite heavy wove paper ; surfaced dyed pale blue and pale green.
Keywords: Manuscripts, Persian / Michigan / Ann Arbor.; Manuscripts, Arabic / Michigan / Ann Arbor.; Hadith / Poetry / Early works to 1800; Hadith / Criticism, interpretation, etc. / Early works to 1800 / http://id.loc.gov/authorities/subjects/sh2008105464; Hadith / Texts / Early works to 1800 / http://id.loc.gov/authorities/subjects/sh2008105462; Headpieces (layout features) / 19th century. / aat